Water Quality Analysis using Pollution Index Method in Klampok Sub-watershed, Semarang Regency, Indonesia - Eka Putri Sri Suwatanti; Maridi Maridi; Suntoro Suntoro (Universitas Sebelas Maret, 2022)
The Klampok Sub-watershed flows in the Semarang Regency, Central Java, Indonesia, located in the upstream part of the Jragung Watershed, used as a source of irrigation. Klampok Sub-watershed experiences environmental pressures in the form of decreasing water quality because of various human activities. For this reason, this study aims to determine the changes in the water quality and pollution index of the Klampok Sub-watershed in 2016 and 2020. The water quality observations were carried out in 2020 utilizing the Total Suspended Solids (TSS), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Nitrate, Zinc (Zn) and Copper (Cu) parameters. The laboratory analysis results were compared with water quality standards based on Government Regulation Number 22 of 2021 and the status of water quality based on the pollution index method under the Decree of the Minister of the Environment Number 115 of 2003. The study results showed a change in the quality and index of water pollution in 2016 and 2020. The study results revealed a decrease in the value of water quality on the parameters BOD, COD, Zn and Cu, which indicated that the water quality was improving. Moreover, the Klampok Sub-watershed pollution index decreased in 2016 and 2020 so that the Klampok Sub-watershed had quality criteria for lightly polluted water to moderately polluted to lightly polluted at each sampling point. Therefore, several efforts to control pollution and management of the Klampok Sub-watershed, such as community outreach, water quality monitoring and industrial compliance, are expected to improve so that the Klampok Sub-watershed's sustainability can provide various benefits to the community.